Polymerized oil and its manufacturing method
By incorporating polymerized oils with specific properties into asphalt, the challenges of expanding the useful temperature range, regenerating degraded asphalt, and ensuring polymer compatibility are addressed, resulting in enhanced asphalt performance and reduced environmental impact.
Patent Information
- Application Number
- JP2023179243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-02-27
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2036-02-26
AI Technical Summary
The asphalt industry faces challenges in enhancing the performance of new asphalts and pavements, particularly in expanding the useful temperature range (UTI), regenerating degraded asphalt, and ensuring compatibility of elastomeric thermoplastic polymers with asphalt.
The development of polymeric oils with specific properties, such as an oligomer content of 2-80% by weight, a polydispersity index of 1.30-2.20, and a sulfur content of 0.001-8% by weight, achieved through a process involving heating biorenewable oils and reacting them with sulfur-containing compounds. These polymerized oils are then incorporated into asphalt for various applications.
The use of polymerized oils significantly enhances the performance of asphalt by expanding its useful temperature range, regenerating degraded asphalt binders, and improving the compatibility of elastomeric polymers with asphalt, leading to improved durability and reduced environmental impact.
Smart Images

Figure 0007662740000014 
Figure 0007662740000015 
Figure 0007662740000016
Abstract
Description
[Technical Field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Patent Application No. 62 / 126,064, filed February 27, 2015, which is incorporated herein by reference in its entirety.
[0002] The present disclosure relates to polymerized oils and methods for polymerizing and blending the oils into asphalt to enhance the performance of new asphalt and / or pavements containing recycled and aged bituminous materials. [Background technology]
[0003] Recent technological challenges facing the asphalt industry have created opportunities for the introduction of agricultural products to improve overall asphalt performance. Such performance improvements can include extending the useful temperature window (UTI) of asphalt, regenerating aged asphalt, and compatibilizing elastomeric thermoplastic polymers in asphalt. Summary of the Invention
[0004] Embodiments described herein provide a polymerized oil comprising a polymer distribution having an oligomer content of from about 2 to about 80 wt. %, a polydispersity index ranging from about 1.30 to about 2.20, and a sulfur content ranging from 0.001 wt. % to about 8 wt. %.
[0005] Another aspect described herein provides a method for polymerizing oil, comprising heating a biorenewable, pre-modified or functionalized oil to at least 100°C, adding a sulfur-containing compound to the heated oil, and reacting the sulfur-containing compound with the oil to produce a polymerized oil comprising a polymer distribution having an oligomer content of about 2 to about 80 wt%, a polydispersity index ranging from about 1.30 to about 2.20, and a sulfur content ranging from 0.001 wt% to about 8 wt%.
[0006] Yet another embodiment described herein provides for the incorporation of polymerized oils into asphalt paving, roofing and coating applications. [Brief explanation of the drawings]
[0007] [Figure 1] Figure 1 shows the complex modulus curve of asphalt as a function of reduced load frequency. [Figure 2] Figure 1 shows the complex modulus curve of asphalt as a function of reduced load frequency. [Figure 3] A comparison of DSC specific heat curves is shown. DETAILED DESCRIPTION OF THE INVENTION
[0008] "Flash point" or "flash point temperature" is the lowest temperature at which a substance will first ignite with a slight flame. It is measured according to ASTM D-92 method using a Cleveland Opening and reported in degrees Celsius (°C).
[0009] "Oligomer" is defined as a polymer with a number average molecular weight (Mn) greater than 1000. Monomers account for all others and include monoacylglycerides (MAG), diacylglycerides (DAG), triacylglycerides (TAG) and free fatty acids (FFA).
[0010] "Performance Grade" (PG) is defined as the temperature range for which a particular asphalt product is designed. For example, an asphalt product designed for temperatures as high as 64°C and as low as -22°C has a PG of 64-22. Performance grade standards are set by the American Association of State Highway and Transportation Officials (AASHTO) and the American Society for Testing Materials (ASTM).
[0011] The "polydispersity index" (also known as "molecular weight distribution") is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn). Polydispersity data are collected using a gel permeation chromatography instrument equipped with a Waters 510 pump and a 410 differential refractometer. Samples are prepared at approximately 2% concentration in THF solvent. A flow rate of 1 ml / min and a temperature of 35°C are used. The columns consist of 50, 100, 1000, and 10000 Angstroms Phenogel 5 micrometer linear / mixed guard columns and a 300 x 7.8 mm Phenogel 5 micrometer column (styrene-divinylbenzene copolymer). Molecular weights were determined using the following standards: JPEG0007662740000001.jpg43165
[0012] The "useful temperature range" (UTI) is defined as the interval between the highest and lowest temperatures for which a particular asphalt product is designed. For example, an asphalt product designed for temperatures as high as 64°C and as low as -22°C has a UTI of 86. In road paving applications, the seasonal and geographic extremes of temperature determine the UTI for which an asphalt product must be designed. The UTI of asphalt is measured by a series of AASHTO and ASTM standard tests developed by the Strategic Highway Research Program (SHRP), also known as "Performance Grade" (PG) standards.
[0013] Asphalt and bituminous materials For purposes of this invention, asphalt, asphalt binder, and bitumen refer to the binding phase of an asphalt pavement. Bituminous material refers to a blend of asphalt binder and other materials (e.g., aggregate or filler). Binders used in this invention can be materials obtained from asphalt-producing refineries, fluxes, refinery vacuum tower bottoms, pitch and other residues from vacuum tower bottoms processing, as well as oxidized and aged asphalt from recycled bituminous materials, such as reclaimed asphalt pavement (RAP) and recycled asphalt shingles (RAS).
[0014] Starting Oil Material Biorenewable oils may be used as the starting oil material. Biorenewable oils can include oils separated from plants, animals, and algae.
[0015] Examples of vegetable-based oils can include, but are not limited to, soybean oil, linseed oil, canola oil, rapeseed oil, castor oil, tall oil, cottonseed oil, sunflower oil, palm oil, peanut oil, safflower oil, corn oil, corn distillers bottoms, lecithin (phospholipids), and combinations thereof, as well as crude streams thereof.
[0016] Examples of animal-based oils can include, but are not limited to, animal fats (eg, lard, tallow) and lecithin (phospholipids), and combinations thereof, and crude streams thereof.
[0017] Biorenewable oils can also include partially hydrogenated oils and stand oils through conjugation, where heteroatoms are not derived, such as, but not limited to, diacylglycerides, monoacylglycerides, free fatty acids, alkyl esters of fatty acids (e.g., methyl, ethyl, propyl, and butyl esters), diol and triol esters (e.g., ethylene glycol, propylene glycol, butylene glycol, trimethylolpropane), and mixtures thereof. An example of a biorenewable oil can be waste cooking oil or other used oil.
[0018] Pre-modified or functionalized oils can also be used as starting oil materials. Examples of pre-modified oils are those that have been pre-vulcanized or polymerized by other polymerization techniques (e.g., maleic anhydride or acrylic acid modification, hydrogenation, dicyclopentadiene modification, conjugation via reaction with iodine, transesterification, or treatment to modify acid value, hydroxyl value, or other properties). Some examples of pre-modified oils are polyol esters (e.g., polyglycerin esters or castor oil esters) or estolides. Such modified oils can be mixed with unmodified vegetable or animal oils, fatty acids, glycerin, and / or lecithin. Examples of functionalized oils are those to which heteroatoms (oxygen, nitrogen, sulfur, and phosphorus) have been introduced.
[0019] In a preferred embodiment, the starting oil material is reclaimed corn oil (usually the residual liquid resulting from the manufacturing process of converting corn into ethanol) (also known as "corn distillers bottoms") or other low-cost waste oil. In another preferred embodiment, the starting oil material comprises free fatty acids. Those skilled in the art will appreciate that where high functionality is desired, vegetable-based oils with higher levels of unsaturation can be used.
[0020] Sulfur cross-linking of oil In various embodiments, polymerization of biorenewable, pre-modified, or functionalized oils is achieved by crosslinking the glyceride fraction of fatty acid chains and / or triglyceride molecules contained in the biorenewable, pre-modified, or functionalized oil using a sulfur-containing compound. The sulfur in the sulfur-containing compound is preferably in reduced form. The polymerization method includes the steps of (a) heating the biorenewable, pre-modified, or functionalized oil; (b) adding a sulfur-containing compound to the heated oil; and (c) reacting the sulfur-containing compound with the oil to produce a polymerized oil having a desired polymer distribution (having an oligomer content of about 2 to about 80 wt%), a polydispersity index (about 1.30 to about 2.20), and a sulfur content (between 0.001 wt% and about 8 wt%).
[0021] In the first step, the biorenewable, pre-modified, or functionalized oil is heated to at least 100°C in a vessel equipped with an agitator. In a more preferred embodiment, the biorenewable, pre-modified, or functionalized oil (which may collectively be referred to herein as "oil") is heated to at least 115°C. In a preferred embodiment, the sulfur-containing compound is added portionwise to the heated biorenewable, pre-modified, or functionalized oil and can be added in solid or molten form, although it is understood that the sulfur-containing compound can be added before or simultaneously with the oil. In a preferred embodiment, the sulfur-containing compound can be elemental sulfur, but is not limited to such. The reaction between the sulfur and the oil essentially raises the temperature of the oil-sulfur mixture, and in a preferred embodiment, the reaction is maintained between about 130°C and about 250°C, more preferably between about 130°C and about 220°C, and even more preferably between about 160°C and about 200°C during the reaction.
[0022] The oil-sulfur mixture can be continuously sparged with a gas-containing stream during the polymerization reaction between the oil and sulfur. The gas-containing stream can be selected from the group consisting of nitrogen, air, and other gases. The gas-containing stream can help promote the reaction and can also help reduce odors associated with the reaction (HS and other sulfides) in the final product. The use of air can be beneficial in addition to the sulfurization process, as it can cause oxidative polymerization of the oil.
[0023] Optionally, a promoter can be used to increase the rate of this reaction. Examples of promoters include, but are not limited to, zinc oxide, magnesium oxide, and dithiocarbamates.
[0024] The reaction can be continued and continuously monitored using gel permeation chromatography (GPC) and / or viscosity until the desired degree of polymerization is obtained as described below.
[0025] The robustness of the sulfur crosslinking reaction and its ability to be used for the polymerization of low-cost raw materials containing high free fatty acid content and residual moisture are advantages of this polymerization method compared to other methods, offering flexibility in starting material selection.
[0026] Polymerization characteristics The reaction between the sulfur-containing compound and the biorenewable, pre-modified or functionalized oil is allowed to proceed until a polymer distribution is obtained having between about 2% and about 80% by weight oligomer (20% to 98% by weight monomer), more preferably between about 15% and about 60% by weight oligomer (40% to 85% by weight monomer), and even more preferably between about 20% and about 60% by weight oligomer (40% to 80% by weight monomer). In an even more preferred embodiment, the polymer distribution ranges from about 50% to about 75% by weight oligomer and about 25% to about 50% by weight monomer.
[0027] The polydispersity index of the polymerized oil is in the range of about 1.30 to about 2.20, more preferably about 1.50 to about 2.05.
[0028] The effect of the reactions described herein is a low sulfur content in the resulting polymerized oil. In some embodiments, the sulfur content comprises less than 8% by weight of the polymerized oil. In other embodiments, the sulfur content comprises less than 6% by weight of the polymerized oil. In still other embodiments, the sulfur content comprises less than 4% by weight of the polymerized oil. In other embodiments, the sulfur content comprises less than 2% by weight of the polymerized oil. However, the sulfur content comprises at least 0.001% by weight of the polymerized oil.
[0029] The resulting polymerized oil has a flash point of at least about 100° C. and no more than about 400° C., as measured using the Cleveland Open Method. In some embodiments, the flash point of the polymerized oil is between about 200° C. and about 350° C. In other embodiments, the flash point of the polymerized oil is between about 220° C. and about 300° C. In still other embodiments, the flash point of the polymerized oil is between about 245° C. and about 275° C. The polymerized oils described herein may have higher flash points than their starting oil materials, especially when compared to other polymerization processes.
[0030] The viscosity of the polymerized oil varies based on the type of starting oil material, but generally ranges from about 1 cSt to about 100 cSt at 100°C.
[0031] end use In one aspect, the present invention provides a modified asphalt and a method for producing the same, comprising a blend of 60% to 99.9% by weight of an asphalt binder and 0.1% to 40% by weight of a polymerized oil, the polymerization of the oil being achieved by sulfur crosslinking as described above. The modified asphalt can be used for road paving or roofing applications.
[0032] In another aspect, the present invention provides a modified asphalt and a method for producing the same, comprising a blend of 60% to 99.9% by weight of an asphalt binder and 0.1% to 40% by weight of a polymerized oil, wherein the polymerized oil is a blend of polymerized oil obtained by sulfur crosslinking as described above and one or more of the biorenewable, pre-modified or functionalized oils described above (e.g., unmodified vegetable oils, animal oils, fatty acids, fatty acid methyl esters, gums or lecithin, and gums or lecithin of modified oils or other oils, or fatty acids).
[0033] In addition to polymerized oil, other ingredients can be mixed with the asphalt binder to create a modified asphalt, including, but not limited to, thermoplastic elastomeric and plastomeric polymers (styrene-butadiene-styrene, ethylene vinyl acetate, functionalized polyolefins, etc.), polyphosphoric acid, anti-stripping additives (amine-based, phosphate-based, etc.), warm mix additives, emulsifiers, and / or fibers. Typically, these ingredients are added to the asphalt binder / polymerized oil in amounts ranging from about 0.1% to about 10% by weight.
[0034] Asphalt modification Declining bitumen quality increases the need for the addition of chemical modifiers to improve the quality of asphalt products. Heavy mineral oils from petroleum refineries are the most commonly used modifiers. These mineral oils extend the low-temperature limit of the asphalt product by "plasticizing" the binder, but this also tends to reduce the high-temperature limit of the asphalt.
[0035] Mineral flax oils, crude petroleum distillates, and re-refined mineral oils have been used in attempts to soften asphalt. In many cases, the use of such materials results in a reduction in the asphalt's high-temperature modulus, exceeding its low-temperature modulus, making the asphalt more susceptible to rutting at high temperatures. This effect results in a reduction in the useful temperature window (UTI).
[0036] Mineral flux oils, petroleum crude distillates, and re-refined mineral oils often have volatile fractions at pavement application temperatures (e.g., 150-180°C), generally have lower flash points than asphalt, and may be more prone to loss of performance due to oxidative degradation.
[0037] The polymerized oils and blends described herein have further demonstrated that they are not only viable alternatives to mineral oils, but also extend the UTI of asphalt to a greater extent than other performance modifications, thereby providing significant value to asphalt producers. The observed increase in UTI using the polymerized oils described herein is a unique property not seen with other asphalt-softening additives (e.g., asphalt flux, heavy oil, or flash oil). Generally, a grade improvement based on either the SHRP Performance Grade (PG) standard or the penetration grade system used in many countries is achieved with approximately 2-3 wt.% polymerized oil based on the weight of asphalt. For example, the increase in UTI observed with the addition of approximately 3 wt.% polymerized oil is as much as 4°C, thus providing a broader PG modification range, allowing the lower temperature limit to be lowered without sacrificing the upper temperature limit.
[0038] Regeneration of deteriorated bituminous materials Asphalt deteriorates primarily through a combination of oxidation and volatilization mechanisms. Aging increases asphalt modulus, reduces viscous damping and stress relaxation, and increases brittleness at low performance temperatures. As a result, asphalt becomes more susceptible to cracking and damage accumulation. The increasing use of recycled and reclaimed bituminous materials, including highly deteriorated asphalt binders from sources such as recycled asphalt pavement (RAP) and recycled asphalt shingles (RAS), has created a need for "rejuvenating additives" that can partially or completely restore the rheological and fracture properties of aged asphalt. Asphalt deterioration has also shown increased colloidal instability and phase incompatibility by increasing the content of high molecular weight, highly polar, insoluble "asphaltenes" that can further bind. The use of polymerized oils described herein is particularly useful in RAP and RAS applications. The polymerized oils described herein function as compatibilizers for asphalt fractions, particularly in aged and oxidized asphalt, resulting in a well-balanced and stable asphalt binder with restored performance and durability.
[0039] During plant production, asphalt is subjected to high temperatures (usually between 150-190°C) and exposure to air where significant oxidation and volatilization of light fractions can occur, resulting in increased modulus and viscous behavior. The aging process is simulated using a rolling thin film oven (ASTM D2872), where a rolling thin film of asphalt is exposed to a jet of heated air at approximately 163°C for approximately 85 minutes. Rheological properties are measured by measuring |G after aging versus before aging. * Following ASTM D7175 using the ratio of | / sinδ, the G * is the complex modulus of elasticity, and δ is the phase angle. * | / sinδ) vs. (|G * The larger the ratio of | / sinδ), the greater the effect of oxidative deterioration and volatilization of the tested asphalt.
[0040] Using this process, asphalt treated with the polymerized oil or blends thereof described in this invention has been shown to have a lower rate and therefore a downward trend in rheological property changes as a result of oxidative degradation and volatilization.
[0041] Thus, the polymerized oils described herein have been found to be capable of restoring aged asphalt binders and modifying the rheological properties of less aged asphalt binders, thereby enabling the incorporation of high levels of aged recycled asphalt into pavements and other applications using smaller amounts of polymerized oil, potentially resulting in significant economic savings and a reduced environmental impact of paving due to the reduced use of new resources.
[0042] Compatibilization of elastomeric thermoplastic polymers with asphalt. Asphalt is often modified with thermoplastic elastomeric and plastomeric polymers, such as styrene-butadiene-styrene (SBS), to increase high-temperature modulus and resilience, enhance resistance to heavy traffic loads, and toughen the asphalt base against damage accumulation due to repeated loading. Such polymers, typically used in amounts of 3-7% by weight of the asphalt, are high-shear blended into the asphalt at temperatures above 180°C and "cured" at similar temperatures, during which the polymer swells by adsorption of the lighter fractions of the asphalt until it forms a continuous volume phase in the asphalt.
[0043] The volume phase of fully cured polymer, influenced by the degree of polymer compatibility in the asphalt and the fineness of the dispersed particles, results in increased specific area and improved swelling properties due to increased interface between the asphalt and polymer.
[0044] It has been shown that the polymerized oils described herein can enable further compatibilization of the elastomeric polymer into the asphalt when the oil is added and mixed into the asphalt prior to the polymer incorporation or curing stage. This is particularly effective for asphalt binders that are poorly compatible with the elastomeric polymer. Additionally, the oil can aid in the light ends swelling the polymer during curing.
[0045] Warm-temperature additives and asphalt In recent years, an increasing proportion of pavements are manufactured using what are commonly referred to as "warm-temperature additives" to produce "warm-temperature" asphalt pavements. Warm-temperature pavements can be manufactured and compacted at lower manufacturing temperatures, require less compaction to achieve a target mix density, and thus retain the properties necessary for compaction at lower temperatures, allowing for an increase in the maximum transport distance of the asphalt mix from the plant to the construction site.
[0046] The different mechanisms by which warm-up additives provide benefits include increased lubrication of aggregates during compaction of the asphalt mix, reduced binder viscosity at production temperatures, and better coating and wetting of aggregates. Thus, a wide range of chemicals and additives can exhibit one or more of the properties attributed to warm-up additives when added to asphalt mixes.
[0047] The polymerized oils described herein can be used as warm-up additives and / or compaction aids to obtain many of the benefits expected from a warm-up additive, including minimal reductions in manufacturing and application temperatures due to increased aggregate lubrication and aggregate wettability. In such applications, the additives are preferably used in amounts ranging between about 0.1 and 2% by weight of the bitumen. [Example]
[0048] The following examples are presented to illustrate the present invention and to assist one of ordinary skill in making and using the same. The examples are not intended to limit the scope of the invention in any way.
[0049] Experimental Method A quantity of precipitated sulfur (ranging in mass from 6.5 g to 56.5 g) is added to a 1-liter round-bottom flask containing 650 g of vegetable oil. The reaction vessel is then heated to the target reaction temperature using a heating mantle, taking care not to exceed the target temperature by more than 5°C. The reaction mixture is stirred using an electric stirrer equipped with a stirring shaft and blades. The reaction is continuously sparged with nitrogen at 2 to 12 standard cubic feet per hour (SCFH). A condenser and receiving flask are used to collect any distillate.
[0050] Note that when sulfur dissolves in the oil, it produces a foamy material at about 110-115°C. To measure oligomer content and distribution, the reaction is monitored using GPC, and viscosity is measured at 40°C using ASTM D445. The reaction is considered complete when the desired oligomer content is obtained. The reaction vessel is then cooled to 60°C.
[0051] Example 1: Polymerized Palm Oil Modified Asphalt #1 Modified asphalt binders include: 97.0% by weight pure (i.e., unmodified) asphalt binder graded to standard grade PG64-22 (and "true" grade PG64.88-24.7). Note: True grade refers to the exact temperature at which the asphalt meets the control specification, which always meets and exceeds the corresponding standard grade (i.e., true high temperature grades are always higher than standard high temperature grades, and true low temperature grades are always lower than standard low temperature grades). 3.0 wt% sulfurized refined palm oil reacted with 3 wt% elemental sulfur at 160°C for 5 hours under nitrogen sparge, resulting in a modifier with the following properties: Oligomer 31.8% Viscosity of 17.2 cSt at 100°C ·Polydispersity index (PDI) approx. 1.30
[0052] After annealing the binder at 150°C for 1 hour, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 4.8°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a 0.8°C improvement in the useful temperature range. Details are shown in Table 1. JPEG0007662740000002.jpg42162 1 UTI: Usable Temperature Range is the difference between the high temperature performance grade and the low temperature performance grade, as measured using AASHTO M320. 2 O-DSR: High temperature performance grade of unaged ("new") asphalt binder measured using a dynamic shear rheometer (DSR) following ASTM D7175 and AASHTO M320. 3 R-DSR: High temperature performance grade of rolling thin film oven aged (RTFO after ASTM D2872) asphalt binder measured using a dynamic shear rheometer (DSR) following ASTM D7175 and AASHTO M320. 4 S-BBR: A low temperature performance grade controlled by the creep stiffness parameter ("S") measured on asphalt binders using both a rolling thin film oven (ASTM D2872) and a pressure aging tester (ASTM D6521) sequentially using a bending beam rheometer following ASTM D6648 and AASHTO M320. 5 m-BBR: A low temperature performance grade controlled by the creep rate parameter ("m") measured on asphalt binders using both a rolling thin film oven (ASTM D2872) and a pressure aging tester (ASTM D6521) sequentially using a bending beam rheometer following ASTM D6648 and AASHTO M320.
[0053] Example 2: Polymerized Palm Oil Modified Asphalt #2 Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0 wt% sulfurized refined palm oil reacted with 4 wt% elemental sulfur at 160°C for 20.5 hours under nitrogen sparge, resulting in a modifier with the following properties: Oligomer 56.18% Viscosity of 25.0 cSt at 100°C PDI approx. 1.50
[0054] The binder was annealed at 150°C for 1 hour, after which the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 5.9°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a 1.5°C improvement in the useful temperature range. Details are shown in Table 2. JPEG0007662740000003.jpg43157
[0055] Example 3: Sulfurized Recovered Corn Oil Modified Asphalt #1 Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0 wt% sulfurized recovered corn oil (RCO) reacted with 1.5 wt% elemental sulfur for 7 hours at 160°C under nitrogen sparge, resulting in a modifier with the following properties: Oligomer 16.0% PDI approx. 1.50
[0056] After annealing the binder for 1 hour at 150°C, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 6.0°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a 0.4°C improvement in the useful temperature range. Details are shown in Table 3. JPEG0007662740000004.jpg38167
[0057] Example 4: Sulfurized Recovered Corn Oil Modified Asphalt #2 Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0 wt% sulfurized recovered corn oil (RCO) reacted with 6.0 wt% elemental sulfur for 6 hours at 160°C under nitrogen sparge, resulting in a modifier with the following properties: Oligomer 50.3% Viscosity at 40°C is 270cSt PDI approx. 2.19
[0058] The binder was annealed at 150°C for 1 hour, after which the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 4.4°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a 0.7°C improvement in the useful temperature range. Details are shown in Table 4. JPEG0007662740000005.jpg38164
[0059] Example 5: Asphalt #1 modified with sulfurized refined sunflower oil blend Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0% by weight of a blend having: 14.5 wt% sulfurized refined sunflower oil reacted with 7.0 wt% elemental sulfur at 160°C for 19 hours under nitrogen sparge. This resulted in a modifier with 70.8% oligomers. Refined sunflower oil 85.5% by weight The blend of sulfurized oil and unmodified oil had an oligomer content of 11.9%, a viscosity of 55 cSt at 40°C, and a PDI of approximately 1.64.
[0060] After annealing the binder for 1 hour at 150°C, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 5.3°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a significant improvement in low temperature grade, with no change in the useful temperature range. Details are shown in Table 5. JPEG0007662740000006.jpg43169
[0061] Example 6: Asphalt #2 modified with sulfurized refined sunflower oil blend Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0% by weight of a blend having: 53.9 wt% sulfurized refined sunflower oil reacted with 7.0 wt% elemental sulfur at 160°C for 19 hours under nitrogen sparge. This resulted in a modifier with 70.8% oligomers. Refined sunflower oil 46.1% by weight The blend of sulfurized oil and unmodified oil has an oligomer content of 42.76%, a viscosity of 177 cSt at 40°C, and a PDI of approximately 3.16.
[0062] The binder was annealed at 150°C for 1 hour, after which the modifier was mixed into the asphalt. The modification resulted in a 4.8°C low temperature grade improvement, bringing the net binder grade from PG64-22 to PG58-28. Performance grade testing was performed according to AASHTO M320. The net change between the high-performance and low-performance grades resulted in a 0.1°C improvement in the useful temperature range. Details are shown in Table 6. JPEG0007662740000007.jpg46164
[0063] Example 7: Asphalt #3 modified with sulfurized refined sunflower oil blend Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0% by weight of a blend having: 63.4 wt% sulfurized refined sunflower oil reacted with 7.0 wt% elemental sulfur at 160°C for 19 hours under nitrogen sparge. This resulted in a modifier with 70.8% oligomers. Refined sunflower oil 36.6% by weight The blend of sulfurized oil and unmodified oil had an oligomer content of 48.3%, a viscosity of 254 cSt at 40°C, and a PDI of approximately 3.55.
[0064] After annealing the binder for 1 hour at 150°C, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 5°C improvement in low temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a 0.8°C improvement in the useful temperature range. Details are shown in Table 7. JPEG0007662740000008.jpg39164
[0065] Example 8: Asphalt #1 modified with a blend of refined sunflower oil and palm oil Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0% by weight of a blend having: 14.5 wt% sulfurized refined sunflower oil reacted with 7.0 wt% elemental sulfur at 160°C for 19 hours under nitrogen sparge. This resulted in a modifier with 70.8% oligomers. Palm oil 84.5% by weight The blend of sulfurized oil and palm oil has an oligomer content of approximately 11.9%. PDI is approximately 1.77
[0066] After annealing the binder at 150°C for 1 hour, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 5°C improvement in low temperature grade, bringing the pure binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a slight reduction in the useful temperature range by only 0.2°C. Details are shown in Table 8. JPEG0007662740000009.jpg45164
[0067] Example 9: Asphalt #2 modified with a blend of sulfurized refined sunflower oil and palm oil Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7). 3.0% by weight of a blend having: 59.0 wt% sulfurized refined sunflower oil reacted with 7.0 wt% elemental sulfur at 160°C for 19 hours under nitrogen sparge. This resulted in a modifier with 70.8% oligomers. Palm oil 41.0% by weight The blend of sulfurized oil and unmodified oil has an oligomer content of approximately 43% and a PDI of approximately 2.37.
[0068] After annealing the binder for 1 hour at 150°C, the modifier was mixed into the asphalt. Performance grade testing was performed according to AASHTO M320. The modification resulted in a 4.2°C improvement in low temperature grade, bringing the pure binder grade from PG64-22 to PG58-28. The net change between the high-performance and low-performance grades resulted in a slight reduction in the useful temperature range by only 0.1°C. Details are shown in Table 9. JPEG0007662740000010.jpg40164
[0069] Example 10: Asphalt modified with sulfurized soybean fatty acid oil ("acidified soap stock") Modified asphalt binders include: · 97.0% by weight pure asphalt binder graded PG64-22 (true PG64.88-24.7).
[0070] 3.0 wt.% sulfurized refined soybean fatty acid oil was reacted with 5.0 wt.% elemental sulfur at 160°C for 8 hours under nitrogen sparge. This resulted in a modifier with 28.14% oligomers, a viscosity of 167 cSt at 40°C, and a PDI of approximately 2.36. The binder was annealed at 150°C for 1 hour before being blended into asphalt. Performance grade testing was performed in accordance with AASHTO M320. The modification resulted in a 3.3°C improvement in low-temperature grade, bringing the net binder grade from PG64-22 to PG58-28. The net change between the high- and low-performance grades resulted in a 1.5°C decrease in the useful temperature range. This example highlights the potential undesirable effect of free fatty acid content on modifier performance, as it was significantly less effective at improving low-temperature performance grade compared to the dripping that occurs with the high-temperature grade. Details are provided in Table 10. JPEG0007662740000011.jpg42164
[0071] Example 11: Asphalt #1 modified with styrene-butadiene-styrene and sulfurized recovered corn oil as compatibilizers Modified asphalt binders include: · 92.41 wt% pure asphalt binder graded PG64-22 (true PG64.88-24.7). Linear styrene-butadiene-styrene (SBS) 5.5% by weight 0.09% by weight of elemental sulfur (used as SBS crosslinker in asphalt binder) 2.0 wt% sulfurized recovered corn oil (RCO) as described in Example #3 Mixing Instructions: 1. After the binder was annealed at 150°C for 1 hour, the modified binder was mixed into the asphalt. The modified binder was heated to about 193°C for polymer modification. 2. While adding the SBS (within 1 minute), the RPM of the high shear mixer was set to 1000. Immediately after polymer addition, the RPM was briefly increased to 3000 rpm for approximately 10 minutes to ensure sufficient grinding of the SBS pellets, after which the shear level was reduced to 1000 rpm. 3. Polymer mixing was continued at 1000 rpm for a total of 2 hours. 4. The temperature was reduced to about 182°C at 150 rpm, whereupon the sulfur crosslinker was added. 5. Mixing was continued for 2 hours at 182°C and 150 rpm. 6. The polymerized binder was placed in an oven at 150°C for approximately 12-15 hours (overnight) to obtain sufficient swelling of the polymer.
[0072] Performance grade testing was performed according to AASHTO M320. Multiple stress creep and recovery tests were performed according to AASHTO T350 on the unaged binder at 76°C and the RTFO residue at 64°C. The results show that despite a decrease in modulus, the average percent binder recovery increased in binders containing the modifier, demonstrating the effectiveness of the modifier as a compatibilizer for SBS, resulting in better distribution of the same mass of elastomeric polymer compared to binders without the modifier and therefore a more efficient elastic network. Details are shown in Table 11. JPEG0007662740000012.jpg58164
[0073] Example 12: Regeneration of highly deteriorated sphalt binder using oil from Example #3 The example shown in Figure 1 shows the complex modulus (G) of asphalt as a function of reduced loading frequency measured using a dynamic shear rheometer (DSR) following ASTM D7175. * ) curves are shown. Measurements were taken on samples of the asphalt binder (PG64-22) used in Example #3 after three levels of laboratory aging. Degradation Level 1: Oxidative degradation in a rolling thin film oven at 163°C for 85 minutes (following ASTM D2872). Degradation Level 2: Continuous degradation of the specimen after Degradation Level 1 by subjecting it to oxidative degradation for 20 hours at 100°C and 2.1 MPa air pressure using a pressure degradation tester (following ASTM D6521). In accordance with the performance grade standard, 20 hours of PAV degradation accelerates the simulated degradation that typically occurs during the performance life of an asphalt pavement. Deterioration Level 3: Successive deterioration of the specimen after Deterioration Levels 1 and 2 by subjecting it to an additional 20 hours of oxidative deterioration using a Pressurized Aging Tester (PAV) for a total of 40 hours of PAV deterioration, representing the deterioration level of the binder from a severely deteriorated pavement.
[0074] FIG. 1 shows that further degradation from Level 1 to Level 2 and from Level 2 to Level 3 results in a significant increase in the complex modulus across a reduced frequency spectrum.
[0075] The asphalt binder at aged level 3 was "regenerated" by heating the binder to 150°C for 1 hour and incorporating 5% by weight of the total binder of oil from Example #3. The curve corresponding to the regenerated binder in Figure 1 shows that regeneration reduced the G of the aged asphalt across the entire spectrum of frequencies. * The results show that the rheological properties of the binder are significantly lower than those of aged asphalt binder.
[0076] Example 13: Regeneration of highly deteriorated sphalt binder using oil from Example #4 The example shown in Figure 1 shows the complex modulus (G) of asphalt as a function of reduced loading frequency measured using a dynamic shear rheometer (DSR) following ASTM D7175. * ) curves. Measurements were taken of a sample of the asphalt binder (PG64-22) used in Example #3 after laboratory aging to the three levels described in Example 12, which show that further aging results in a significant increase in the complex modulus across a reduced frequency spectrum.
[0077] The asphalt binder at aged level 3 was "regenerated" by heating the binder to 150°C for 1 hour and incorporating 5% by weight of the total binder of oil from Example #4. The curve corresponding to the regenerated binder in Figure 2 shows that regeneration reduced the G of the aged asphalt across the entire spectrum of frequencies. * It has been shown that the rheological properties of low grade aged asphalt binders are reduced.
[0078] Example 14: Effect of sulfurized oil on glass transition The low-temperature performance of asphalt is known to be significantly affected by the asphalt's glass transition temperature, which occurs over the range of performance temperatures often experienced in winter (approximately -5 to -40°C). Furthermore, the rate of physical hardening of asphalt is known to be closely related to the asphalt's glass transition, with the maximum rate occurring at T. Therefore, it is desirable to have a low glass transition temperature to reduce the likelihood that the asphalt will reach the glass transition during its performance life. Aging is known to increase the glass transition temperature of asphalt, and therefore, a desirable property of an effective rejuvenating additive is to lower the glass transition of aged asphalt once mixed.
[0079] The first measurement was performed on a sample of PG64-22 asphalt binder after severe laboratory aging. The laboratory aging consisted of 85 minutes in a rolling thin film oven at 163°C (ASTM D2872), followed by 40 hours of oxidative aging at 100°C and 2.1 MPa air pressure using a pressure aging tester (following ASTM D6521), to demonstrate the level of degradation of the binder from the severely aged pavement. The sample is labeled "Aged Asphalt" in Figure 1. The second sample, labeled "Aged Asphalt + Polymerized Oil," consisted of the following: 95% by weight of the above mentioned PG58-28 pure binder 5 wt% sulfurized recovered corn oil (RCO) reacted with 1.5 wt% elemental sulfur at 160°C for 7 hours under nitrogen sparge, resulting in a modifier with 16.0% oligomers and a PDI of approximately 1.50. Thermal analysis of the binder before and after revitalization with polymerized oil shows that the modifier significantly shifted the Tg of the aged asphalt to lower temperatures, as shown in Table 12. A comparison of the DSC specific heat curves is shown in Figure 3. JPEG0007662740000013.jpg33165
Claims
1. Modified asphalt, (a) 60 to 99.9 weight percent asphalt binder; (b) a blend of 0.1 to 40 wt. % of a polymerized oil crosslinked with a sulfur-containing material and one or more of an unmodified biorenewable oil and a previously modified or functionalized oil, the polymerized oil comprising: i. a polymer distribution having an oligomer content of 2 to 80 wt.%; ii. a polydispersity index in the range of 1.30 to 2.20; and iii. The modified asphalt contains less than 8% by weight of sulfur.
2. 10. The modified asphalt of claim 1 further comprising at least one of the group consisting of thermoplastic elastomeric and plastomeric polymers, polyphosphoric acid, anti-stripping additives, warming additives, emulsifiers, and fibers.
3. The modified asphalt of claim 1 or 2, further comprising recycled asphalt pavement cuttings.
4. The modified asphalt of any one of claims 1 to 3, wherein the unmodified biorenewable oil comprises palm oil, sunflower oil, corn oil, soybean oil, canola oil, rapeseed oil, linseed oil, tung oil, castor oil, tall oil, cottonseed oil, peanut oil, safflower oil, corn distillers bottoms, lecithin (phospholipids), and combinations thereof, and crude streams thereof.
5. The modified asphalt of any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil material selected from the group consisting of palm oil, sunflower oil, corn oil, soybean oil, canola oil, rapeseed oil, linseed oil, tung oil, castor oil, tall oil, cottonseed oil, peanut oil, safflower oil, corn distillers bottoms, and combinations thereof, and crude streams thereof.
6. The modified asphalt of any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil material selected from the group consisting of triacylglycerides, diacylglycerides, monoacylglycerides, and combinations thereof.
7. The modified asphalt according to any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil material containing phospholipids.
8. The modified asphalt of any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil material comprising animal fat.
9. The modified asphalt according to any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil material comprising a vegetable oil.
10. The modified asphalt according to any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil containing free fatty acids.
11. The modified asphalt according to any one of claims 1 to 4, wherein the polymerized oil is derived from a starting oil containing partially hydrogenated oil.
12. The modified asphalt according to any one of claims 1 to 11, wherein the polymerized oil has a sulfur content of less than 6% by weight.
13. The modified asphalt according to any one of claims 1 to 12, wherein the polymerized oil has a sulfur content of less than 4% by weight.
14. The modified asphalt according to any one of claims 1 to 13, wherein the polymerized oil has a sulfur content of less than 2 wt%.
15. The modified asphalt according to any one of claims 1 to 14, wherein the modified asphalt is for paving purposes.
16. The modified asphalt according to any one of claims 1 to 14, wherein the modified asphalt is for roofing applications.
17. The modified asphalt according to any one of claims 1 to 16, wherein the sulfur-containing material comprises elemental sulfur.
Citation Information
Patent Citations
Bituminous compound fob pavement
JP1978111323A
JPP6652973B
JPP6665195B
JPP6857605B
JPP7113096B